Osmolyte concentrations of marine osmoconformers under low salinity stress from a systematic review and meta-analysis - Podbielski, Imke Anna; Schmittmann, Lara; Sanders, Trystan; Melzner, Frank (In: Podbielski, IA et al. (2023): Systematic review and meta-analysis investigating osmolyte concentrations of marine osmoconformers under low salinity stress [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958457, 2023)
This table contains a list of studies that report concentrations for multiple organic osmolytes. These concentrations were calculated into proportions of the total organic osmolyte pool and grouped by taxa (shown in figure 8 of Podbielski et al. 2022). If the sum deviates from 100% this may be caused by using the values for total solute given in the respective papers whenever they were reported. Here, slight deviations from 100% maybe due to rounding errors. Larger deviations are likely caused when total solutes and specific osmolytes were quantified with different techniques. For example, total solutes are sometimes determined as Ninhydrine-positive substances or quaternary ammonium compounds. This may include methylamines or other free amino acids which are not determined via targeted techniques to measure amino acids (i.e. via amino acid analyser). The column "Osmolyte, other" combines values for compounds (<5%) and, if present, values for other compounds, which were data given by the respective papers.
Keywords: cellular volume regulation; marine invertebrates; meta-analysis; osmoconformer; osmolytes; osmoregulation; Osmotic stress; salinity tolerance; systematic review